Opinion of Midwifery School Students About Termination of Pregnancy Without Medical Indication: An Example of a Public University - Balcı, Işılay; Güdücü, Neriman; Sönmez, Aybars Deniz; Aktürk, Sibel Ocak; Öner, Dilara; Dolgun, Gülümser; Çetin, Gürsel (The Bulletin of Legal Medicine, 2022)
Objective:  Termination of pregnancies without medical indications, causes debates in terms of humanitarian, ethical and religious values. In this context, the aim of our study is to investigate the perspectives/opinions of midwifery students regarding unindicated pregnancy terminations.Material and Method:  In this descriptive cross-sectional study, 329 students participated. A 17-question questionnaire form prepared in line with the literature was used. In the analysis of the data, number-percentage distribution, mean, standard deviation and chi square test were used.Results: In marriage, termination of pregnancies up to 10th weeks in health institutions with the consent of the person is more accepted as the class of students increases. In the same circumstances, the idea that the legal period for termination of pregnancy should be less than 10 weeks increased as the class increased.  Termination of pregnancies after 10th week has been rejected with high rates by all grades. At the same time, the idea of terminating the pregnancy by the mother regardless of gestational age and punishing the mother if the father's consent is not obtained is accepted in all classes. However, the idea that it is appropriate to terminate pregnancies as a result of rape in authorized health institutions without observing legal limits is accepted in all classes.Conclusion: It was determined that students' perspectives on termination of pregnancy other than medical necessity differed between classes. The main reason for the differences was thought to be the theoretical and practical knowledge of the students, which increased from the 3rd grade.
Keywords: Termination of pregnancy; Midwifery students; difference between semester